Comparación de complicaciones por sangrado en resección transuretral de próstata con y sin participación de residentes - Valdevenito S., Juan Pablo; Reyes O., Diego; Valdevenito S., Raúl; Gómez G., Álvaro; Cuevas T., Miguel Ángel; Osorio M. , Francisco (Revista Hospital Clínico Universidad de Chile, 2008)
Introduction: transurethral resection of the prostate (TURP) is still the gold standard treatment of prostatic obstruction. The objective of the present study is to compare the bleeding complications of TURP with and without the participation of residents. Material and methods: The data was obtained from a prospective protocol that included 200 patients submitted to TURP. Eleven patients were excluded from the study (5,5%). No patient was lost from follow-up. Results: We reviewed 189 surgeries, 46 with resident participation (24,3%). The operations performed by residents were more prolonged, and required more days with bladder drainage. The followingbleeding complications were observed: 1) Bladder catheter washing to solve obstruction by clots: 11,6%, 2) Endoscopic revision in severe hematuria: 2,6%, 3) Readmission to the hospital in complete urinary retention secondary to clots: 2,1% and 4) Blood transfusion: 2,1%. The transfusion rate was significantly higher in resident surgeries (6,5% versus 0,7%, p=0,045),without differences in the other bleeding complications. Conclusion: The rate of bleeding complications is comparable to that recently published. Applying strict criterion for blood transfusion, no difference was observed between the groups. At our institution, the process of teaching and learning TURP does not increase significantly the risk of bleeding complications.